Aging Time Effects on the Mechanical Properties of Al 6061-T6 Alloy - Rajaa, S. M.; Abdulhadi, H. A.; Jabur, K. S.; Mohammed, G. R. (Engineering, Technology & Applied Science Research, 2018)
This work investigates the influence of artificial aging and solution heat treatment on the hardness and tensile strength (mechanical properties) of Al 6061-T6 alloy. For this investigation, several aluminum 6061-T6 alloy specimens were prepared following the ASTM 176000 recommendations. The prepared specimens were heated for 1 hour at 500ºC before being water-quenched. The procedure for artificial aging was performed for 1, 2, 3, and 4 hours at 190ºC before being slowly cooled in air. Several mechanical and characterization studies were performed on the treated specimens, including an investigation on their microstructure, tensile strength, hardness, and X-ray diffraction pattern. From the results, the strength and hardness properties of the specimens were found to be generally improved, even as the best features were obtained after 2 hours of artificial aging.